Solving of the long-term question: resurrection of Dinodon yunnanensis Werner, 1922 (Squamata: Colubridae: Lycodon) - Vogel, Gernot; Liu, Shuo; David, Patrick; Nguyen, Tan Van (Zootaxa, 2024)
We apply an integrative taxonomic approach, including analyses of molecular and morphological data, along with examination of available type materials, to address the longstanding questioned taxonomic status of Dinodon yunnanensis Werner, 1922, currently considered a junior synonym of Lycodon fasciatus (Anderson, 1879). Based on our data, we revalidate Dinodon yunnanensis, under the combination Lycodon yunnanensis (Werner, 1922) comb. nov. According to the new taxonomic status of Lycodon yunnanensis comb. nov, we restrict the distribution of Lycodon fasciatus to Northeastern India, Central Bhutan, Northern and Central Myanmar, Western and Southwestern Yunnan of China, Northwestern Thailand, Northern Laos, and Northwestern Vietnam. We suggest that Lycodon yunnanensis comb. nov should be considered Least Concern (LC) following the IUCN’s Red List categories. Further studies reassessing the populations of the Lycodon fasciatus complex in Xizang of China is required.